The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00114-015-1320-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, secretion composition, and ecological aspects of stipular colleters in Rubiaceae species from tropical forest and savanna

Abstract: Colleters are secretory structures that produce and release mucilage or a mucilage-resin mixture protecting meristems and young structures against desiccation, herbivores, and pathogens. The secretions may vary in colleters of same or different types, indicating that the functionality of colleters may be more specific than previously thought. In this study, we compared 17 Rubiaceae species from savanna and forest environment focusing on colleter secretions and its ecological role. First, we evaluated the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The presence of chlorenchyma is recorded for the first time in Borreria, Diodia, Galianthe, Manettia, and Oldenlandia. Tresmondi et al (2015) mentioned this tissue in stipules of Richardia grandiflora, and we also observed it in stipules and calyx of Richardia brasiliensis.…”
supporting
confidence: 65%
See 4 more Smart Citations
“…The presence of chlorenchyma is recorded for the first time in Borreria, Diodia, Galianthe, Manettia, and Oldenlandia. Tresmondi et al (2015) mentioned this tissue in stipules of Richardia grandiflora, and we also observed it in stipules and calyx of Richardia brasiliensis.…”
supporting
confidence: 65%
“…The presence of colleters on the internal surface of the calyx and stipules is common in other tribes of the Rubiaceae, even in Rubioidae (e.g., on the stipules of Psychotria L., tribe Psychotrieae; Miguel et al 2009;Vitarelli and Santos 2009;Tresmondi et al 2015). The latter pattern is also found in Cephalanthus occidentalis L. of the tribe Naucleeae (Cinchonoideae; Rutishauser 1983) and in species of Gardenieae (Ixoroideae), such as Randia L. (Judkevich et al 2015;Tresmondi et al 2015). In other Gardenieae, the co-occurrence of colleters inside the stipules and calyx is very common, such as in Gardenia J. Ellis (Dave et al 1988;Low and Wong 2007), Cordiera A.…”
Section: Distribution Of Colleters On Calyx Stipules and Bracteolesmentioning
confidence: 99%
See 3 more Smart Citations